PENGARUH IDEALISME, KECERDASAN EMOSIONAL, DAN ETHICAL SENSITIFTY TERHADAP PENGAMBILAN KEPUTUSAN ETIS CALON PROFESIONAL AKUNTAN (Studi Pada Mahasiswa Prodi Akuntansi Universitas Syiah Kuala) - STIE Lhokseumawe (JAKTABANGUN: Jurnal Akuntansi dan Pembangunan, 2020)
This study aims to determine (1) the influence of Idealism on Ethical Decision Making of Professional Accountant Candidates, (2) the influence of Emotional Intelligence on Ethical Decision Making of Professional Accountant Candidates, (3) the effect of etichal sensitivity on Ethical Decision Making of Professional Accountant Candidates, (4) Idealism, Emotional Intelligence, and Ethical Sensitivity to the Ethical Decision Making of Prospective Professional Accountants. The independent variables in this study are Idealism (X1), Emotional Intelligence (X2), etichal sensitivity (X3), while the dependent variable is the Ethical Decision of Prospective Professional Accountants. Sampling using a purposive sampling technique. The classic assumption test uses the normality test, linearity test, heteroscedasticity test, and multicollinearity test. Hypothesis tests used include simple regression analysis and multiple regression analysis. Based on the results of the study: (1) Idealism has a significant positive effect on the Ethical Decision Making of Prospective Professional Accountants. (2) Emotional intelligence has a significant positive effect on the Ethical Decision Making of Prospective Professional Accountants. (3) etichal sensitivity has a significant positive effect on the Ethical Decision Making of Prospective Professional Accountants. (4) Idealism, emotional intelligence and ethical sensitivity have a significant positive effect on the Ethical Decision Making of Prospective Professional Accountants.